Alzheimer ’s Disease: Possible Mechanisms Behind Neurohormesis Induced by Exposure to Low Doses of Ionizing Radiation - Bevelacqua, J.J. (J Biomed Phys Eng, 2018)
In 2016, scientists reported that human exposure to low doses of ionizing radiation (CT scans of the brain) might relieve symptoms of both Alzheimer’s disease (AD) and Parkinson disease (PD). The findings were unbelievable for those who were not familiar with neurohormesis. X-ray stimulation of the patient’s adaptive protection systems against neurodegenerative diseases was the mechanism proposed by those authors. Now, some more recent studies performed in the field of neurobiological research confirm that low levels of stress can produce protective responses against the pathogenic processes. This paper outlines possible protective consequences of LDR in preventing the pathogenesis of AD through mechanisms such as restoring the myelin sheath and preventing neurodegeneration caused by oxidative stress. Focal demyelination is frequently reported in the proximity of beta-amyloid plaques within neocortex. Extracellular accumulation of amyloid is among well-characterized pathological changes in AD. It should be noted that LDR has been shown to contribute to the regeneration and functional recovery after transverse peripheral nerve injury (through inducing increased production of VEGF and GAP-43), which advances both the axonal regeneration and myelination. Another mechanism which is possibly involved is preventing neurodegeneration caused by oxidative stress. While high doses can induce reactive oxygen species (ROS) formation, oxidative stress and neuro-inflammation, substantial evidence now indicates that LDR can mitigate tissue damage through antioxidant defenses. Although adult neurogenesis has been reported to be beneficial for the regeneration of nervous system, some studies demonstrate that neurogenesis increases in AD brains. In spite of these reports, cellular therapy is introduced as a promising strategy for AD, and hence, LDR can affect the proliferation and differentiation of neural stem cells. Although such mechanisms are not fully known yet, it is hoped that this paper would foster further investigation into the mechanisms of this phenomenon, which accordingly improves human health.